2018
DOI: 10.1136/jech-2017-209456
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood looking glass: 360º automated characterisation of the built environment for neighbourhood effects research

Abstract: BackgroundNeighbourhood quality has been connected with an array of health issues, but neighbourhood research has been limited by the lack of methods to characterise large geographical areas. This study uses innovative computer vision methods and a new big data source of street view images to automatically characterise neighbourhood built environments.MethodsA total of 430 000 images were obtained using Google’s Street View Image API for Salt Lake City, Chicago and Charleston. Convolutional neural networks wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 38 publications
2
39
0
Order By: Relevance
“…A study of 249,405 USA elderly (≥65 years) also found greenness significantly reduced diabetes mellitus risk; an increase in NDVI from 1 SD less to 1 SD more than mean was associated with a reduced risk of 14% for diabetes mellitus [14]. Likewise, another three cross-sectional studies conducted in USA [15], the United Kingdom [18], and Canada [20] observed increased neighborhood or street green space was significantly associated with lower individual diabetes mellitus prevalence. Additionally, several cohort studies have also documented a significant and inverse relationship between greenness levels and diabetes mellitus incidence [9,16].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study of 249,405 USA elderly (≥65 years) also found greenness significantly reduced diabetes mellitus risk; an increase in NDVI from 1 SD less to 1 SD more than mean was associated with a reduced risk of 14% for diabetes mellitus [14]. Likewise, another three cross-sectional studies conducted in USA [15], the United Kingdom [18], and Canada [20] observed increased neighborhood or street green space was significantly associated with lower individual diabetes mellitus prevalence. Additionally, several cohort studies have also documented a significant and inverse relationship between greenness levels and diabetes mellitus incidence [9,16].…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have explored the associations of greenness exposure with glucose levels, insulin resistance, and diabetes mellitus risk, but showed inconsistent results [8][9][10][11][12][13][14][15][16][17][18][19][20]. For example, cross-sectional studies conducted in Netherlands, Australia, the United States, the United Kingdom, and Canada have found that green space had a protective effect on diabetes mellitus [13][14][15]17,18,20], while a cross-sectional study among the Norwegian population found no significant association [8]. Two prospective cohort studies from England and Canada observed a significant association between increased greenness exposure and lower relative hazard of developing diabetes mellitus [9,16], but the Framingham study did not find such a longitudinal association [11].…”
Section: Introductionmentioning
confidence: 99%
“…Methods for identifying street intersections and retrieving and labeling GSV images have been published previously [14,15]. Briefly, latitude and longitude data coordinates for all U.S. street intersections were obtained from the 2017 Census Topologically Integrated Geographic Encoding and Referencing (TIGER) data.…”
Section: Data Sources Google Street View Data For Built Environment Imentioning
confidence: 99%
“…Image resolution was 640 × 640 pixels. Images were processed using trained Visual Geometry Group (VGG-16 model) deep convolutional networks [30,31] (previously detailed by Nguyen et al [15]) to identify the five built environment features of interest (one network per feature). Accuracy of the recognition tasks (comparing the images labeled using this machine learning approach compared with assessment by a human reviewer) ranged from 85 to 93%, and these figures were consistent with a separate, semi-supervised learning approach.…”
Section: Data Sources Google Street View Data For Built Environment Imentioning
confidence: 99%
See 1 more Smart Citation